Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1152/ajpregu.00438.2015
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous distension elicits a blood pressure raising reflex in young and middle-aged adults

Abstract: Wenner MM, Farquhar WB. Peripheral venous distension elicits a blood pressure raising reflex in young and middle-aged adults. Am J Physiol Regul Integr Comp Physiol 310: R1128 -R1133, 2016. First published April 6, 2016 doi:10.1152/ajpregu.00438.2015.-Distension of peripheral veins in humans elicits a pressor and sympathoexcitatory response that is mediated through group III/IV skeletal muscle afferents. There is some evidence that autonomic reflexes mediated by these sensory fibers are blunted with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Another aspect to be considered involves the fact that venous distension-induced pain may contribute to the pressor and neural responses observed in this study. In contrast to others (10,28), in our study, participants reported, on average, mild to moderate pain during saline infusion, suggesting that nociception may contribute to the magnitude of pressor and neural responses to venous distension. However, a similar level of pain was observed between the groups, minimizing its influence on the findings of the study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Another aspect to be considered involves the fact that venous distension-induced pain may contribute to the pressor and neural responses observed in this study. In contrast to others (10,28), in our study, participants reported, on average, mild to moderate pain during saline infusion, suggesting that nociception may contribute to the magnitude of pressor and neural responses to venous distension. However, a similar level of pain was observed between the groups, minimizing its influence on the findings of the study.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, women presented a positive chronotropic effect in the postinfusion period. The HR behavior has similarly been described in previous studies (8,28) and indicates that chronotropic changes may be evoked via mechanical activation of type III and IV venous afferents (19). Similarly, a positive inotropic effect was observed in both groups, as indicated by an increase in CO.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Data were analyzed with LabChart 7 software (ADInstruments, Colorado Springs, Colorado, USA), or exported from LabChart and analyzed with a custom designed LabVIEW program (Matthews et al, 2016). This custom LabVIEW program was used to extract synchronized beat-by-beat data of MSNA, blood pressure, and ECG R-wave time.…”
Section: Methodsmentioning
confidence: 99%
“…The MSNA signal was analyzed offline using a custom LabVIEW program as done previously (Matthews et al, 2016). This program identifies MSNA bursts by an R-wave gating approach.…”
Section: Methodsmentioning
confidence: 99%